Assessment of the relationship between synaptic density and metabotropic glutamate receptors in early Alzheimer’s disease: a multi-tracer PET study - Elaheh Salardini; Ryan S. O’Dell; Em Tchorz; Nabeel B. Nabulsi; Yiyun Huang; Richard E. Carson; Christopher H. van Dyck; Adam P. Mecca (Alzheimer’s Research & Therapy)
Abstract Background The pathological effects of amyloid β oligomers (Aβo) may be mediated through the metabotropic glutamate receptor subtype 5 (mGluR5), leading to synaptic loss in Alzheimer’s disease (AD). Positron emission tomography (PET) studies of mGluR5 using [18F]FPEB indicate a reduction of receptor binding that is focused in the medial temporal lobe in AD. Synaptic loss due to AD measured through synaptic vesicle glycoprotein 2A (SV2A) quantification with [11C]UCB-J PET is also focused in the medial temporal lobe, but with clear widespread reductions is commonly AD-affected neocortical regions. In this study, we used [18F]FPEB and [11C]UCB-J PET to investigate the relationship between mGluR5 and synaptic density in early AD. Methods Fifteen amyloid positive participants with early AD and 12 amyloid negative, cognitively normal (CN) participants underwent PET scans with both [18F]FPEB to measure mGluR5 and [11C]UCB-J to measure synaptic density. Parametric distribution volume ratio (DVR) images using equilibrium methods were generated from dynamic images. For [18F]FPEB PET, DVR was calculated using equilibrium methods and a cerebellum reference region. For [11C]UCB-J PET, DVR was calculated with a simplified reference tissue model – 2 and a whole cerebellum reference region. Results A strong positive correlation between mGluR5 and synaptic density was present in the hippocampus for participants with AD (r = 0.81, p < 0.001) and in the CN group (r = 0.74, p = 0.005). In the entorhinal cortex, there was a strong positive correlation between mGluR5 and synaptic density in the AD group (r = 0.85, p < 0.001), but a weaker non-significant correlation in the CN group (r = 0.36, p = 0.245). Exploratory analyses indicated more widespread significant positive correlations between synaptic density and mGluR5 within regions, as well as significant positive correlations between synaptic density in the temporal lobe and mGluR5 across a broader set of regions commonly affected by AD. Conclusions Our findings suggest that mGluR5 reduction in AD is closely linked to synaptic loss. Longitudinal studies are needed to clarify causality, deepen understanding of AD pathogenesis, and aid in developing novel biomarkers and treatments.